The protective effect of pericytes on vascular permeability after hemorrhagic shock and their relationship with Cx43 - He, Shuangshuang; Zhang, Zisen; Peng, Xiaoyong; Wu, Yue; Zhu, Yu; Wang, Li; Zhou, Henan; Li, Tao; Liu, Liangming (Frontiers in Physiology, 2022)
Vascular hyperpermeability is a complication of hemorrhagic shock. Pericytes (PCs) are a group of mural cells surrounded by microvessels that are located on the basolateral side of the endothelium. Previous studies have shown that damage to PCs contributes to the occurrence of many diseases such as diabetic retinopathy and myocardial infarction. Whether PCs can protect the vascular barrier function following hemorrhagic shock and the underlying mechanisms are unknown. A hemorrhagic shock rat model, Cx43 vascular endothelial cell (VEC)-specific knockdown mice, and VECs were used to investigate the role of PCs in vascular barrier function and their relationship with Cx43. The results showed that following hemorrhagic shock, the number of PCs in the microvessels was significantly decreased and was negatively associated with an increase in pulmonary and mesenteric vascular permeability. Exogenous infusion of PCs (106 cells per rat) colonized the microvessels and improved pulmonary and mesenteric vascular barrier function. Upregulation of Cx43 in PCs significantly increased the number of PCs colonizing the pulmonary vessels. In contrast, downregulation of Cx43 expression in PCs or knockout of Cx43 in VECs (Cx43 KO mice) significantly reduced PC colonization in pulmonary vessels in vivo and reduced direct contact formation between PCs and VECs in vitro. It has been suggested that PCs have an important protective effect on vascular barrier function in pulmonary and peripheral vessels following hemorrhagic shock. Cx43 plays an important role in the colonization of exogenous PCs in the microvessels. This finding provides a potential new shock treatment measure.